Odpowiedzi

2010-03-22T16:00:22+01:00
A) 4/√5+2= 4√5-8/5-4= 4√5-8
b) 2/3-√7= 2-√7/3
c) 3/-5+2√5= -15-6√5/25-20=-15-6√5/5
d) 10/3√2-4=30√2+40/2=15√2+20
e) √3/5√3+8= 15-8√3/11
f)2√6/8-3√6= 16√6+36/10
g)1+√3/2+√3=2-√3+2√3-3/4-1=√3-1
h)√5-2/3-√5=√5-1/4
2010-03-22T16:10:19+01:00
Najlepsza Odpowiedź!
2010-03-22T16:29:46+01:00

a)4/√5+2 = 4(√5-2) / (√5+2)(√5-2) = 4√5-8 / √25-4 = 4(√5-2)/5-4 = 4(√5-2)

b)2/3-√7 = 2(3+√7)/(3-√7)(3+√7) = 2(3+√7)/9-7 = 2(3+√7)/2 = 3+√7

c)3/-5+2√5 = 3(-5-2√5)/(-5+2√5)(-5-2√5) = 3(-5-2√5)/25-20 = 3(-5-2√5)/5 = (-15-6√5)/5

d)10/3√2-4 = 10(3√2+4)/(3√2-4)(3√2+4) = 10(3√2+4)/18-16 = 10(3√2+4)/2 = 5(3√2+4)

e)√3/5√3+8 = √3(5√3-8)/(5√3+8)(5√3-8) = √3(5√3-8)/75-64 = √3(5√3-8)/11

f)2√6/8-3√6 = 2√6(8+3√6)/(8-3√6)(8+3√6) = 2√6(8+3√6)/64-54 = 2√6(8+3√6)/10 = √6(8+3√6)/5

g)1+√3/2+√3 = (1+√3)(2-√3)/(2+√3)(2-√3) = (2-√3+2√3-3)/4-3 = (√3-1)/1 = √3-1

h)√5-2/3-√5 = (√5-2)(3+√5)/(3-√5)(3+√5) = (3√5+5-6-2√5)/9-5 = (√5-1)/4